PERANAN SISTEM ENTERPRISE RESOURCES PLANNING (ERP) DALAM MENINGKATKAN KINERJA KEUANGAN PERUSAHAAN: STUDI LITERATUR - Bunga Ramadani Nureza Saputri; Siti Atia Tulloh; Putri Fatimah Azzahra; Febriana Haudi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Companies are currently required to have fast, accurate, and integrated information systems to be able to compete in the digital era. Enterprise Resource Planning (ERP) is one of the systems widely implemented because it can integrate various business processes ranging from finance, production, marketing, to human resources. This research is a literature review that aims to examine the role of ERP systems in improving company financial performance. The results of various journal findings indicate that ERP implementation can increase operational efficiency, accelerate the reporting process, reduce unnecessary costs, and help management make decisions based on more accurate data. Furthermore, several studies analyzed in this research also confirm that ERP helps companies reduce human error in the process of recording and processing data. With data integration, each division can be connected, so that company activities become more transparent. This has an impact on improving the quality of financial reports, which are more timely and easier to use to evaluate company performance. ERP implementation has also been proven to support companies in increasing work productivity, because time-consuming manual processes can be automated to become more efficient. Overall, this literature review concludes that ERP has a positive impact on company financial performance, both directly and indirectly. However, ERP effectiveness is still influenced by factors such as human resource readiness, management support, and the suitability of ERP modules to the company's needs. By understanding these factors, companies can maximize the benefits of ERP as a long-term investment to improve financial performance and market competitiveness.